EGFR immunohistochemistry as biomarker for antibody-based therapy of squamous NSCLC: experience from the first ring trial of the German Quality Assurance Initiative for Pathology (QuIP®) - Petersen, Iver; Schirmacher, Peter; Warth, Arne; Lasitschka, Felix (Pathology, research and practice, 2017)
Background EGFR and its downstream signaling pathway are important targets for cancer therapy. Recently, the monoclonal anti-EGFR antibody Necitumumab in combination with gemcitabine and cisplatin was approved (EMA/14106/2016) for first-line treatment of squamous non-small cell carcinoma (SqNSCLC). Eligibility was restricted to cases with positive EGFR expression. In this context, a ring trial of the Quality Assurance Initiative for Pathology (QuIP®) was launched to prepare the German pathology community for a reliable and reproducible, immunohistochemically based biomarker test. Materials and methods The trial was set up by a three-step approach. Two lead institutes were nominated to organize the trial process and to select appropriate cancer samples. These were first tested by the H-score (range 0-300) to identify positive and negative cases. Seven additional pathology institutes with experience in EGFR immunohistochemistry each tested the selected panel of identical cases (internal ring trial) to confirm the suitability of samples and scoring criteria. Then the open ring trial for all institutes of pathology in German speaking countries was announced. Results For the internal trial 8 EGFR-positive and 2 negative lung sqNSCLC samples were selected. A cut-off value of cell membranous staining in≥1% of tumor cells was introduced to define a case as EGFR negative or positive. Two points were attainable per correctly assessed sample leading to a maximum of 20 points,≥18 points were required for a successful participation. All 7 panel institute passed this barrier, 5 with the maximum of 20 points and two with one error (18 points) being related to one case with incorrect interpretation of cytoplasmic versus membranous staining and one case with an H-score of 2 as being considered EGFR positive. A second cut-off value (H-score≥3) was therefore introduced. In the open ring trial, 34 institutions participated of which 28 were successful according to the above criteria. The trial revealed a high reproducibility despite the use of different EGFR antibodies and detection systems. There was no association between technical parameters and trial failure. Again, one participant misinterpreted the subcellular EGFR localization. Conclusions The first nationwide ring test for determination of EGFR IHC expression in sqNSCLC could be successfully performed in a very tight time frame. By this, the national pathology community was prepared to incorporate this marker in the panel of predictive cancer tests in a quality assessed manner and to initiate and accompany future studies on EGFR pathway pathology.